Introducing RDA : a guide to the basics - Oliver, Chris 1951-; American Library Association; ebrary, Inc. (Chicago : American Library Association, 2010)
Practical advice for catalogers and library administrators on how to make the transition from the Anglo-American cataloging rules (AACR) to Resource description and access (RDA).
What is RDA? -- RDA and the international context -- FRBR and FRAD in RDA -- Continuity with AACR2 -- Where do we see changes? -- Implementing RDA -- Advantages, present and future.
Includes bibliographical references (p. 105-109) and index.
Electronic reproduction.
Keywords: Resource description & access; Anglo-American cataloguing rules; Descriptive cataloging -- Standards; Cataloging -- Standards; Electronic books